Bile Acids in Neurodegenerative Disorders - Ackerman, Hayley D.; Gerhard, Glenn S. (Frontiers in Aging Neuroscience, 2016)
Bile acids, a structurally related group of molecules derived from cholesterol, have a long history as therapeutic agents in medicine, from treatment for primarily ocular diseases in ancient Chinese medicine to modern day use as approved drugs for certain liver diseases. Despite evidence supporting a neuroprotective role in a diverse spectrum of age-related neurodegenerative disorders, including several small pilot clinical trials, little is known about their molecular mechanisms or their physiological roles in the nervous system. We review the data reported for their use as treatments for neurodegenerative diseases and their underlying molecular basis. While data from cellular and animal models and clinical trials support potential efficacy to treat a variety of neurodegenerative disorders, the relevant bile acids, their origin, and the precise molecular mechanism(s) by which they confer neuroprotection are not known delaying translation to the clinical setting.